PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASIONAL TERHADAP PEMBELAJARAN ORGANISASIONAL DAN KINERJA DOSEN AKADEMI FARMASI YARSI PONTIANAK - B2042151008, FADLI (Equator Journal of Management and Entrepreneurship (EJME), 2018)
The aim of this research is known to analyze (1) influence of leadership style and organizational commitment to lecturer's performance, (2) influence of style leadership to organizational commitment, (3) influence of leadership style on organizational learning, and (4) influence of organizational commitment to organizational learning. This research was conducted using causal methods with the population for 35 lecturers and 1 director on Akademi Farmasi Yarsi Pontianak. The analysis tool used is the Path Analysis and the research result has shown that (1) leadership style, commitment organizational and organizational learning have a positive influence on lecturer's performance (2) leadership style and organizational commitment have a positive influence on organizational learning. Â Keyword : Leadership Style, Organizational Commitment, Organizational Learning, Lecturer's Performance